TRANSITION PERIODS OF THE PHENOPHASE PROCESSES OF THE INTRODUCED GRAPE CULTIVARS - Fayziev Jamoliddin Nasirovich; Kurbanova Sarvinoz Anvar kizi (Web of Journals Publishing, 2024)
In the article, the periods of transition of phenological phases of the introduced grape cultivars are studied. Growth phases, budding and branch growth; bloom; the growth of bunches; the ripening of bunches; the periods of shedding of leaves are determined. It was noted that the shortest growing season (117-118 days) of the introduced grape varieties for food was observed in the Chukurak and Husayni Kelin Barmak grape varieties. The longest duration (147-153 days) was observed in the Mirney, Hurmane kyzil, Kara janjal and said gulyami varieties, while the intermediate indicator (124-143 days) was observed in the Ak hussayni, Kadu hussayni and Husayni kelin barmak grape varieties.
Keywords: Vine, fооd, variety, vegetation, phenophase, bud, bulge, bunch, flowering, ripening.